Study of Antioxidant Effect in Patients with Type 2 Diabetes - B. Aljaryan , Hajir; Sabah Jabr Sabah Jabr , Huda; Khalil Al-Shamari , Ataa; Abbas Khdhair, Ola; Abdul Redah Al-Kremy , Noor; H. Al-Ameedy , Taif; Salman Al-Juboory , Dhuha (Hammurabi Journal of Medical Sciences, 2024)
Background: Diabetes stands as the predominant etiological factor behind the global prevalence of chronic renal disease. Among the myriad challenges faced by diabetic individuals, oxidative stress looms prominent. The intricate antioxidant system acts as a crucial defense, shielding cells from potential harm induced by these oxidative species. Objectives: This study endeavors to delve into the biochemical milieu; specifically focusing on enzymatic and non-enzymatic antioxidants in subjects afflicted with type 2 diabetes mellitus. Materials and Methods: blood specimens were procured from a cohort of 60 participants, segregated into two cohorts: the patient group encompassing 30 individuals with diabetes, and the control group comprising 30 healthy counterparts. Measures of Random Blood Sugar, HBA1C, Catalase (CAT), Superoxide Dismutase (SOD), and Malondialdehyde (MDA) were undertaken. Results: The outcomes revealed a marked escalation in HBA1C, Random Blood Sugar levels, and Malondialdehyde levels within the patient group in comparison to the control cohort. However, no substantial variance was discerned in Catalase and Superoxide Dismutase levels between the diabetic and healthy groups. Conclusions: The findings underscore a surge in free radical production in diabetic subjects, precipitating diminished antioxidant levels of Catalase and Superoxide Dismutase. Notably, Malondialdehyde emerges as a promising indicator for assessing oxidative stress and holds potential as a discerning marker for the early detection of diabetes.